2015
DOI: 10.4172/2161-1149.1000176
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Levels of Macrophage Derived Cytokine and Matrix Metalloproteinase-9 are associated with Disease Activity in the Patients with Systemic Lupus Erythematosus

Abstract: Aim:The aim of our study was to assess serum concentration of macrophage derived cytokine (MDC) and matrix metalloproteinase-9 (MMP-9) in patients with active and inactive SLE and in healthy volunteers. Subjects and Methods:The study included 40 patients with SLE and 40 healthy control. The serum level of MDC and MMP-9 were evaluated and compared between the patients and the controls. The association of the MDC and MMP-9 with disease activity, renal involvement, drug intake were also evaluated.Results: SLE pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Here in our Egyptian SLE cohort, the levels of serum Gelatinase B/MMP-9 were discovered to be dramatically decreased. This finding is compatible with other studies carried out on Iranian, Poland, Saudi Arabian, Chinese, and Korean SLE cases [ 5 , 31 , 32 , 33 , 34 ]. Whereas it is incompatible with other researchers e.g., Ram et al and Faber-Elmann et al who reported elevated Gelatinase B/MMP-9 in SLE patients’ sera [ 8 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here in our Egyptian SLE cohort, the levels of serum Gelatinase B/MMP-9 were discovered to be dramatically decreased. This finding is compatible with other studies carried out on Iranian, Poland, Saudi Arabian, Chinese, and Korean SLE cases [ 5 , 31 , 32 , 33 , 34 ]. Whereas it is incompatible with other researchers e.g., Ram et al and Faber-Elmann et al who reported elevated Gelatinase B/MMP-9 in SLE patients’ sera [ 8 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…We hypothesized that the advanced SLE disease activity was not caused by the decreased serum levels of MMP-9. Our data are hand in hand with Makowski and Ramsby who found that MMP-9 levels and anti-ds-DNA levels showed an inverse association [ 37 ], and with Faber-Elmann et al who did not see any connection between the blood MMP-9 level and SLEDAI that was significant [ 18 ], but it is in contradiction with Ahmad et al and Liu et al, who demonstrated a negative correlation between MMP-9 serum level and SLEDAI [ 32 , 33 ]. In the current work, the ROC curve pointed out that circulated MMP-9 had an excellent power to discriminate SLE patients from healthy people (AUC = 0.903, accuracy = 86%, and p < 0.001).…”
Section: Discussionmentioning
confidence: 99%